The embroidered Bible : studies in biblical apocrypha and pseudepigrapha in honour of Michael E. Stone - Stone, Michael E., 1938-; DiTommaso, Lorenzo.; Henze, Matthias.; Adler, William, 1951- (Studia in Veteris Testamenti Pseudepigrapha, 2018)
This Festschrift contains forty-one original essays and six tribute papers in honour of Michael E. Stone, Gail Levin de Nur Professor Emeritus of Religious Studies and Professor Emeritus of Armenian Studies at the Hebrew University of Jerusalem. The volume's main theme is Old Testament Pseudepigrapha, envisioned in its broadest sense: apocryphal texts, traditions, and themes from the Second-Temple period to the High Middle Ages, in Judaism, Christianity and, to a lesser extent, Islam. Most essays present new or understudied texts based on fresh manuscript evidence; the others are thematic in approach. The volume's scope and focus reflect those of Professor Stone's scholarship, without a special emphasis on Armenian studies.